Development of a Fixed Wing Unmanned Aerial Vehicle (UAV) for Disaster Area Monitoring and Mapping - Nugroho, Gesang; Taha, Zahari; Nugraha, Tedy Setya; Hadsanggeni, Hatyo (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
The development of remote sensing technology offers the ability to perform real-time delivery of aerial video and images. A precise disaster map allows a disaster management to be done quickly and accurately. This paper discusses how a fixed wing UAV can perform aerial monitoring and mapping of disaster area to produce a disaster map. This research was conducted using a flying wing, autopilot, digital camera, and data processing software. The research starts with determining the airframe and the avionic system then determine waypoints. The UAV flies according to the given waypoints while taking video and photo. The video is transmitted to the Ground Control Station (GCS) so that an operator in the ground can monitor the area condition in real time. After obtaining data, then it is processed to obtain a disaster map. The results of this research are: a fixed wing UAV that can monitor disaster area and send real-time video and photos, a GCS equipped with image processing software, and a mosaic map. This UAV used a flying wing that has 3 kg empty weight, 2.2 m wingspan, and can fly for 12-15 minutes. This UAV was also used for a mission at Parangtritis coast in the southern part of Yogyakarta with flight altitude of 150 m, average speed of 15 m/s, and length of way point of around 5 km in around 6 minutes. A mosaic map with area of around 300 m x 1500 m was also obtained. Interpretation of the mosaic led to some conclusions including: lack of evacuation routes, residential area which faces high risk of tsunami, and lack of green zone around the shore line.